After Iraq where next for the Middle East? - Dyer, Gwynne (Yale University Press, 2008)
American and British troops are not going to stay in Iraq for ever. But what will happen when they start to leave? This book predicts that the Middle East will go through the biggest shake-up since the region became part of the Ottoman Empire and argues that the rest of the world should stand back and leave them to it